Representações de motociclistas sobre riscos e acidentes de trânsito, Belo Horizonte, Minas Gerais - Hercilia Najara Ferreira de Souza (2015)
Traffic accidents in Brazil and worldwide, particularly those involving motorcyclists, emerge in a complex and violent environment that involves more than just the number of people wounded or killed. The multicausality of those accidents shows the importance of focusing on the psychosocial aspects in order to understand how the subjects perceive and react to the risks of traffic. The goal of the study was to understand the social representations of risks and traffic accidents among motorcyclists involved in accidents in Belo Horizonte, Minas Gerais. A qualitative interview study was conducted, grounded on the theory of social representations and building on top of Alan Giami's propositions. Individual, in-depth open interviews were conducted with 16 motorcyclists involved in traffic accidents and subsequently hospitalized in a reference trauma center in Belo Horizonte. Structural analysis of narratives was used to interpret the collected data. The results were separated into three categories: 1) Representations of accidents involving motorcycles; 2) Representations of types of transportation; 3) Representations of city traffic. The analysis reveals that motorcyclists interpret and justify their involvement in accidents in a constant search for cause, blame and factors contributing to the event. The accident is thus represented by its sudden occurrence, by the blame of others and rarely by admitting guilt. Projecting the responsibility for the event is very common in representations of traffic accidents. Everyday experiences, attributes of different vehicles, and most of all involvement in traffic accidents are the basis used to classify transportation types as "safe" or "unsafe". Aspects connected to the structure and size of the vehicle are fundamental to the representations of safe transportation types, but long waiting times, crowded vehicles and limited reach of public rail are seen as obstacles to relying on safe transportation types for daily usage. On the other hand, the speed, agility, fuel savings and ability to 'cheat' traffic are seen as advantages of motorcycles. The fragility of motorcycles, however, is represented as dangerous due to the higher possibility of involvement in risky situations, particularly those that could result in injury to the motorcyclist. Traffic is seen as a "chaotic" environment, with actors having psychosocial characteristics reinforced by the overvaluation of personal transportation, the feeling of invulnerability created by believing traffic accidents only happen to others and the weakened value fairness in interactions in traffic. The representations of traffic situations involving motorcyclists can be used to predict the behavior of the actors: the decision of whether to respect traffic laws or not is based on the risks involved. The ability to handle and overcome adversities in traffic strengthens subjects' ideas of being able to avoid accidents or experiences that induce fear. Subjects are aware of the risks, but those are represented as something that does not concern them because it only happens to others. The results show the necessity of considering the psychosocial aspects of interactions in traffic and how risk is introjected and interpreted by motorcyclists. Programs intended to promote health and prevention of accidents, specially those involving motorcyclists, should be planned with consideration of the complexity of those events, and should strive to reveal the vulnerabilities in the actors in order to promote actions that will reduce the risk of traffic accidents.